Peran Sekolah Dasar dalam Menumbuhkembangkan Perilaku Hidup Bersih dan Sehat pada Siswa di MIN 6 Tangerang - Syifani Yasmin; Een Unaenah; Eka Yulyawan Kurniawan (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
Clean and Healthy Living Behaviour (PHBS) is one of the important efforts in instilling healthy living habits in elementary school students. However, studies on PHBS in schools generally focus more on the role of teachers or school health programs, so the involvement of the entire school community has not been comprehensively examined. This study aims to describe the role of elementary schools in fostering PHBS among students at MIN 6 Tangerang. This study uses a qualitative approach with a phenomenological type. The research informants consist of the principal, teachers, administrative staff, cleaning staff, and students selected purposively. Data were collected through interviews, observations, and documentation, and then analysed through data reduction, data presentation, and drawing conclusions. The study results indicate that the implementation of Clean and Healthy Living Behaviour (PHBS) at MIN 6 Tangerang is carried out through the active involvement of all school members. The principal plays a role in policy formulation and facility provision, teachers contribute to education, habituation, and role modelling, while administrative and cleaning staff support the creation of a clean and healthy school environment. In addition, adequate facilities and various school programs support the formation of clean and healthy living habits among students.